A review on mucoadhesive polymer used in nasal drug delivery system - Mayank Chaturvedi; Manish Kumar; Kamla Pathak (Wolters Kluwer Medknow Publications, 2011)
This update review is on mucoadhesive polymers used in nasal dosage forms. The nasal mucosa provides a potentially good route for systemic drug delivery. One of the most important features of the nasal route is that it avoids first-pass hepatic metabolism, thereby reducing metabolism. The application of mucoadhesive polymers in nasal drug delivery systems has gained to promote dosage form residence time in the nasal cavity as well as improving intimacy of contact with absorptive membranes of the biological system. The various new technology uses in development of nasal drug delivery dosage forms are discussed. The various dosage forms are vesicular carriers (liposome, noisome), nanostructured particles, prodrugs, in situ gelling system with special attention to in vivo studies.